Aislamiento térmico para disminuir el flujo de calor en la superficie lateral del secador de lecho fluidizado de la facultad de industrias alimentarias de la Universidad Nacional de la Amazonía Peruana - Ruiz Caselima, Joyce Marilú (2023)
The objective general of the present work of thesis was: selling off the thermal insulation to decrease the heat flow in the lateral surface of the drier of bed fluidized of the FIA-UNAP. For that matter has come true a revision on the whole information relating to the transferential mechanisms of heat, by means of the one that the relation between the lost heat flow, the thickness of the thermal insulation and the temperature of the lateral surface of the mentioned drier. Finally, came true fifteen (15) simulations of said relation, to observe that the lost heat flow diminishes of insignificant way. Therefore, investigation has quantitative focus, it is somewhat diligent with explanatory level of deepening and I design correlational. The results of fifteen simulations of said relation, show that the lost heat flow, he decreases its value to a large extent from 301.241 W if ??At = 0 m, even 195.748 W if ??At = 0.04 m. From ??At = 0.04 m, the lost heat flow diminishes of insignificant way even 195.557 W if ??At = 0.05 m. For all what's mentioned the lines arrives, it can be said that in the present work of thesis has come true with the general objective lens and in turn he has tried on his general.